Gérard Dion, 1912-1990 - Thwaites, James (Labour / Le Travail, 1991)
The article pays homage to the life and work of Gérard Dion, who for decades played a pivotal role in the department of industrial relations at Laval University as well as its journal, Relations industrielles/Industrial Relations. A Catholic priest, Dion, who also held degrees in sociology and theology, wrote extensively on labour and industrial relations, and was involved at a number of levels in Quebec society. He was the recipient of honours and awards, including the Order of Canada. A photo of Dion is included.
Keywords: DION, Gerard; Obituaries

In Memoriam – Eugene Forsey 1904-1991 - Thwaites, James (Relations industrielles / Industrial Relations, 1991)
Offers a tribute to Forsey's life and work – scholar, labour and political activist, and media commentator.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

La Grève au Québec: Une Analyse quantitative exploratoire portant sur la période 1896-1915 - Thwaites, James (Labour / Le Travail, 1984)
Presents and analyzes statistical data on strikes in Quebec during the period 1896-1915. Concludes that there was a significant increase in strikes as compared to the previous half century, that they took place in particular economic sectors, that they were mostly about seeking rather than protecting existing gains or rights, that they were concentrated in the two major urban centres of Quebec City and especially Montreal, that they occurred in the warmer seasons, and that salaries were the principal issue.

Employers' Associations and Industrial Relations : A Comparative Study - Thwaites, James (Relations Industrielles / Industrial Relations, 1989)
This article reviews the book, "Employers' Associations and Industrial Relations : A Comparative Study," by John P. Windmuller & Alan Gladstone.

Sweated Industries and Sweated Labor : The London Clothing Trades, 1860-1914 - Thwaites, James (Relations Industrielles / Industrial Relations, 1986)
This article reviews the book, "Sweated Industries and Sweated Labor : The London Clothing Trades, 1860-1914," by James A. Schmiechen.

Organization Theory : A Macro Perspective for Managing; Organization Theory : Integrating Structure and Behavior - Thwaites, James (Relations Industrielles / Industrial Relations, 1986)
This article reviews the books, "Organization Theory : A Macro Perspective for Managing," by John H. Jackson, Cyrill P. Morgan, and J.G.P. Prolillo, and "Organization Theory : Integrating Structure and Behavior, by Garry Dessler.

In Search of Excellence : Lessons from America's Best-Run Companies - Thwaites, James (Relations Industrielles / Industrial Relations, 1984)
This article reviews the book, "In Search of Excellence : Lessons from America's Best-Run Companies," by T.J. Peters & R.H. Jr. Waterman.

American Working Class History : A Representative Biography - Thwaites, James (Relations Industrielles / Industrial Relations, 1984)
This article reviews the book, "American Working Class History : A Representative Biography," by Maurice F. Neufeld, Daniel J. Leab & Dorothy Swanson.

Essays in Canadian Business History - Thwaites, James (Relations Industrielles / Industrial Relations, 1984)
This article reviews the book, "Essays in Canadian Business History," by Tom Traves.

Trade Unions in Canada : 1812-1902 - Thwaites, James (Relations Industrielles / Industrial Relations, 1983)
This article reviews the book, "Trade Unions in Canada: 1812-1902," by Eugene Forsey.

An Impartial Umpire : Industrial Relations and the Canadian State 1900-1911 - Thwaites, James (Relations Industrielles / Industrial Relations, 1982)
This article reviews the book, "An Impartial Umpire : Industrial Relations and the Canadian State 1900-1911," by Paul Craven.

Les enseignants et le pouvoir : histoire de l’Alliance des professeurs de Montréal, les luttes syndicales et le développement social (1952-1958) - Thwaites, James (Relations Industrielles / Industrial Relations, 1982)
This article reviews the book, "Les enseignants et le pouvoir : histoire de l’Alliance des professeurs de Montréal, les luttes syndicales et le développement social (1952-1958)," by Paulette Vigeant-Galley.

Business Organizes : The Early Years in Québec - Thwaites, James (Relations Industrielles / Industrial Relations, 1981)

Labour Studies Research Bulletin - Thwaites, James (Relations Industrielles / Industrial Relations, 1981)
This article reviews the book, "Labour Studies Research Bulletin," by Labour Studies Resource Center.

Manuels d’histoire et syndicalisme au Québec - Thwaites, James (Relations Industrielles / Industrial Relations, 1980)

Le monde du travail au Québec : bibliographie = The World of Labour in Québec: Bibliography - Thwaites, James D.; Leblanc, André (Presses de l'Université du Québec, 1996)
5700 titres en francais et en anglais, mais aussi dans d'autres langues. Des milliers d'articles, de livres, de thèses, de documents audio et audiovisuels, ainsi que les journaux du monde ouvrier. Des sources essentielles pour tous ceux et celles qui s'intéressent au monde du travail. --Résumé de l'éditeur
Keywords: Bibliographies; Industrial relations; Industrial relations Québec (Province) Bibliography; Labor; Labor Québec (Province) Bibliography; Labor laws and legislation; Labor laws and legislation Québec (Province) Bibliography; Québec; Relations industrielles Québec (Province) Bibliographie; Syndicalism; Syndicalism Québec (Province) Bibliography; Syndicalisme Québec (Province) Bibliographie; Travail Québec (Province) Bibliographie; Work environment; Work environment Québec (Province) Bibliography